A RARE CASE OF TESTICULAR MIXED GERM CELL TUMOUR WITH POLYEMBRYOMA AND MATURE TERATOMA COMPONENTS - MISHRA, PRAGNYA PARAMITA; PANDA, PREMANAND (International Journal of Current Pharmaceutical Research, 2025)
Polyembryoma of the testis is an extremely rare and distinct form of mixed germ cell tumor with recapitulation of embryoid bodies where yolk sac, embryonal, and teratoma components can be found. Our case is a 27-year-old male presented with a painless mass in the left scrotum, which was progressively increasing over the last 3 mo. Serum Alpha-fetoprotein and beta HCG were marginally elevated. Fine needle aspiration cytology (FNAC) was suggestive of a non-seminomatous germ cell tumor of the testis. Histopathology of the orchidectomy specimen revealed a predominant polyembryoma with an immature teratoma component with a diagnosis of mixed germ cell tumor. Immunohistochemistry confirmed the diagnosis, and the patient was on adjuvant chemotherapy. We are reporting the case because of extreme rarity.